Politeness in "Adit dan Sopo Jarwo" Animation - I Wayan Budiarta; I Gusti Ngurah Adi Rajistha (Lingua Cultura, 2018)
This article aimed to describe the politeness and its violations in the Adit dan Sopo Jarwo program. The data for this research were collected by recording and taking notes. The data that have been taken were analyzed by using the theory of politeness by Leech (2014). The result of the analysis is presented informally, by verbally describing the findings. Related to the types of the politeness, the result of the analysis shows that there are three types of politeness maxim exemplified in the animation; tact, approbation, and generosity. Politeness violations occur with the tact, agreement, and generosity maxims. The utterances that show politeness are uttered by the characters Jarwis, Ujang, Denis, and Mr. Habibie whereas the utterances that show politeness violations are uttered by Ujang, Denis, Devi, and Jarwo.